2008
DOI: 10.1038/nsmb.1453
|View full text |Cite
|
Sign up to set email alerts
|

A second binding site for double-stranded RNA in TLR3 and consequences for interferon activation

Abstract: We show that substrate specificity of Toll-like receptor 3 (TLR3) is due to the presence of two binding sites in the ectodomain, separated by 50 A. This corresponds to two turns of a double-stranded RNA duplex, allowing differentiation between nucleic acids in the A- or B-type conformation. We propose that there are different arrangements of TLR3 ectodomains along the double-stranded RNA that could modulate the strength of the interferon response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…In addition, TLR3 has two distinct binding sites for dsRNA binding, one located from the N terminus to LRR3 and the other in LRR19 through 21 of the ectodomain. Both are required for binding to poly(I:C) (43)(44)(45)(46)(47)(48), in comparison to TLR9 and TLR7, which recognize ligands primarily through one binding site (49). Both cleaved and uncleaved TLR3 appear to be competent for signaling, but proteolytic cleavage may confer additional activity to the recognition of some ligands by TLR3, as we have observed for the recognition of Reovirus dsRNA and poly(A:U) RNA in RAW267.4 cells.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, TLR3 has two distinct binding sites for dsRNA binding, one located from the N terminus to LRR3 and the other in LRR19 through 21 of the ectodomain. Both are required for binding to poly(I:C) (43)(44)(45)(46)(47)(48), in comparison to TLR9 and TLR7, which recognize ligands primarily through one binding site (49). Both cleaved and uncleaved TLR3 appear to be competent for signaling, but proteolytic cleavage may confer additional activity to the recognition of some ligands by TLR3, as we have observed for the recognition of Reovirus dsRNA and poly(A:U) RNA in RAW267.4 cells.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, some structural studies have reported that efficient binding of dsRNA to TLR3 requires a minimum of 40-50 nt (16,37). The recent identification of a second binding site for dsRNA in TLR3 confirms the ability of 21-nt siRNA to bind this immune receptor (38) and helps to resolve some of the conflicting biological and structural data. Our data that 21-nt siRNA phosphorylates TLR3 demonstrate that dsRNAs of this minimum length directly activate this immune sensor.…”
Section: Discussionmentioning
confidence: 84%
“…Because H60A bound dsRNA at pH 5.5, the inability of H60A-transfected reporter cells to respond to dsRNA suggests that the pH of the intracellular compartment in which TLR3 encounters dsRNA is higher than 5.5, consistent with binding occurring in early, but not late endosomes. Interestingly, Pirher et al (12) found that H39R, a mutation that replaces a positively charged imidazole side chain with a positively charged guanidinium group, retained almost full signaling capacity. This was also reflected in binding capacity because the H39R mutant bound dsRNA equivalently to WT TLR3 at pH below 6.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%